Comparing digital finance in the UK, US, India and Nigeria - Peterson K. Ozili (Financial Internet Quarterly, 2020)
This paper examines digital finance usage in the UK, US, India and Nigeria. Using data from the global financial development indicators, the findings reveal that the UK and US have higher digital finance usage than India and Nigeria. The US has higher credit card usage compared to the UK while the UK has higher debit card usage compared to the US. Also, Nigeria has higher debit card usage than India. The findings also show that higher debit card usage is correlated with higher domestic credit to the private sector in the US and Nigeria. Higher credit card usage is correlated with lower domestic credit to the private sector, lower private credit by deposit money banks, and fewer remittances to the UK. The implication of the findings is that policy makers in developing countries should develop the digital finance and payment systems in their countries to close up the wide gap in digital finance adoption between developing and developed countries
Keywords: E44; F65; G18; G21; G28; 330; Fintech; Digital finance; Credit card; Debit card; Payment system; Digital financial services; financial technology; financial institutions